Awareness toward AIDS: A Dental Perspective - Ragavendra, T Raju; Mhaske, Shubhangi; Mandora, Dakshata; Gouraha, Abhishek (Journal of Orofacial Research, 2013)
Background: HIV/AIDS (human immunodeficiency virus/ acquired immunodeficiency syndrome) constitute not only a pathological entity but also have a social implication which notonly affects the general quality of life but also of those who are related to him/her. So, it becomes imperative to facilitate the spread of awareness among the dental professionals to build a stronger foundation against this social taboo. Aims and objectives: To assess the awareness of dental fraternity of Bhopal on HIV/AIDS and to assess and compare the differences and similarities between various groups of dental fraternity. Materials and methods: The study population included 200 individuals. It was divided into three categories as undergraduate (UG) students, postgraduate (PG) students, and dental practitioners. Standardized questionnaire was prepared including open- and close-ended objective type questions. The questionnaire consisted of 17 questions. Questions were based on three groups, i.e. knowledge and awareness, clinical manifestations of HIV and diagnosis and prognosis. Data collected was then transferred to Microsoft excel work sheet and evaluated by SPSS 20.0 version software. Results: From our study we deduced that basic knowledgeabout HIV is 75.5% in dental practitioners as compared to 64 and 36% of UG and PG. Knowledge about diagnosis of HIV in dental fraternity is 35% in UG as compared to 26 and 33% inPG and dental practitioners, knowledge about symptoms and treatment is 70% in UG as compared to 68 and 62% of PG and dental practitioners, awareness about HIV/AIDS is 90% in PG as compared to 80% of UG and dental practitioners. Conclusion: From our study we can safely conclude that the overall knowledge of dentists about HIV/AIDS is adequate, butthere are certain gray areas, such as diagnosis and treatment which need our attentions. It becomes imperative for us to know and be aware of the HIV/AIDS threat. This article attempts to assess and reflect how much we need to improve our education system so as to be foolproof against this virus of mass destruction because forewarned is forearmed.